The Influence of the Critical-Collaborative Learning Model (CCLM) on Students’ Creative Thinking Ability - Tharissa Anita Putri; Irwandani; Sodikin (Wise Education, 2024)
This study aims to determine the effect of the Critical-Collaborative Learning Model (CCLM) on students' creative thinking abilities in thermodynamics material. The research employed a quantitative approach using a quasi-experimental method. The subjects of this study were grade XI students of Madrasah Aliyah Negeri (MAN), with data collection instruments in the form of essay questions designed to measure students' creative thinking abilities. The results indicated that the average score of the experimental class (85.5%) was higher than that of the control class (68.9%). The data were tested for normality and homogeneity, showing that the data were normal and homogeneous. Subsequently, the Independent Sample T-test revealed a significance level of 0.000, which is less than Sig. < 0.05, meaning that H0 is rejected and H1 is accepted. Thus, it can be concluded that the use of the Critical-Collaborative Learning Model (CCLM) significantly affects students' creative thinking abilities.